The Roles of Lithub Website in Learning English Literature for Beginner Literature Students - Kobis, Dewi Christa; Saini, Fadhlan; Tomatala, Michel Farrel (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
This study aims to find the possible roles of Lithub website based on students’ perspectives. It is a typical website that provides all materials and sources of literature including literary works such as short stories and poetries, and literary criticisms. This study implemented a method that required a questionnaire and interviews to gain the data. There were 35 beginner literature students who were in their 3rd semester (when this study was conducted) at the Faculty of Humanities, Universitas Sam Ratulangi participated in this study and 5 of them served as interviewees that had been required by random samplings due to their availability and willingness. This study found that 7 roles can be offered by Lithub website in order to help beginner literature students’ learning process. They are: 1) providing complete learning materials, 2) making learning more interesting by providing lively visualization, 3) providing audio recordings, 4) providing appropriate writing examples by reliable authors and reviewers, 5) improving grammatical competence, 6) train them to conduct literary analysis using literary criticism, and 7) motivates them to read more by providing e-books.        Keywords:     Lithub website, literature, literary analysis, technology.